GE_GERICHTE C/14324/2014 vom 29. September 2017 - GE Cour de justice (2017)
BANQUE ; MANDAT ; CONSEIL EN PLACEMENT ; BANQUE RESTANTE ; SIGNATURE ; QUITTANCE ; EXÉCUTION DE L'OBLIGATION ; RESPONSABILITÉ CONTRACTUELLE | CPC.178; CO.971; CO.398.2;